The study of active geomagnetic shielding coils system for JUNO. (18th October 2021) - Zhang, G.; Lu, H.; Songwadhana, J.; Yan, Y.; Morozov, N.; Ning, F.; Zhang, P.; Yang, C.; Khosonthongkee, K.; Limphirat, A.; Yan, T.; Payupol, T.; et al.
Abstract: The Jiangmen Underground Neutrino Observatory (JUNO) is a large liquid scintillator (LS) detector for neutrino mass ordering and other neutrino physics research. The detector uses large-size 20 inches photomultiplier tubes to detect photons from a liquid scintillator. The large PMTs are sensitive and easily affected such that the detection efficiency loses about 60% under the geomagnetic field intensity (∼500 mG). It has a significantly negative effect on the detector performance, and a compensation system is necessary for geomagnetic field shielding. As permalloys are easily rusted in water, a better way for the geomagnetic shielding is to apply an active compensation coils system. The simulations show that a set of 32 circular coils can meet the experiment requirement. The residual magnetic field is less than 0.05 G in the Central Detector Photomultiplier Tube (CD-PMT) region (38.5–39.5 m in diameter). A prototype coil system with a 1.2 m was built to validate the simulation and the design. The measured data of prototype and simulation results are consistent with each other, and geomagnetic field intensity is effectively reduced by coils, verifying the shielding coils system design for JUNO. This study is expected to provide practical guidance for the PMT magnetic field shielding for future large-scale detector designs.